Improvement in Isolation and Identification of Mouse Oogonial Stem Cells - Zhiyong Lu; Meng Wu; Jinjin Zhang; Jiaqiang Xiong; Jing Cheng; Wei Shen; Aiyue Luo; Li Fang; Shixuan Wang (Hindawi Limited, 2016)
Female germline stem cells (FGSCs) or oogonial stem cells (OSCs) have the capacity to generate newborn oocytes and thus open a new door to fight ovarian aging and female infertility. However, the production and identification of OSCs are difficult for investigators. Rare amount of these cells in the ovary results in the failure of the acquisition of OSCs. Furthermore, the oocyte formation by OSCs in vivo was usually confirmed using tissue sections by immunofluorescence or immunohistochemistry in previous studies. STO or MEF feeder cells are derived from mouse, not human. In our study, we modified the protocol. The cells were digested from ovaries and cultured for 2-3 days and then were purified by magnetic-activated cell sorting (MACS). The ovaries and fetus of mice injected with EGFP-positive OSCs were prepared and put on the slides to directly visualize oocyte and progeny formation under microscope. Additionally, the human umbilical cord mesenchymal stem cells (hUC-MSCs) were also used as feeder cells to support the proliferation of OSCs. The results showed that all the modified procedures can significantly improve and facilitate the generation and characterization of OSCs, and hUC-MSCs as feeder will be useful for isolation and proliferation of human OSCs avoiding contamination from mouse.